Hydronium ion diffusion in model proton exchange membranes at low hydration: insights from ab initio molecular dynamics. Issue 4 (12th January 2021) - Zelovich, Tamar; Winey, Karen I.; Tuckerman, Mark E.
Abstract : Sequence of steps in the reaction of hydronium (H3 O + ) with sulfonate (SO3 − ) contributing to the proton structural diffusion mechanism in a low-hydration environment of a proton-exchange-membrane (PEM) mimic. Abstract : Fuel-cell deployable proton exchange membranes (PEMs) are considered to be a promising technology for clean and efficient power generation. However, a fundamental atomistic understanding of the hydronium diffusion process in the PEM environment is an ongoing challenge. In this work, we employ fully atomistic ab initio molecular dynamics to simulate diffusion mechanisms of the hydronium ion in a model PEM. In order to mimic a precise polymer with a layered morphology, as recently introduced by Trigg, et al., Nat. Mater., 2018, 17, 725, a nano-confined environment was created composed of graphane bilayers to which sulfonate end groups (SO3 − ) are attached, and the space between the bilayers was subsequently filled with water and hydronium ions up to λ values of 3 and 4, where λ denotes the water-to-anion ratio. We find that for the low λ value, the water distribution is not homogeneous, which results in an incomplete second solvation shell for H3 O +, fewer water molecules in the vicinity of SO3 −, and a higher probability of obtaining a coordination number of ∼1 for the nearest oxygen neighbor to SO3 − . These conditions increase the probability that H3 O + will react with SO3 − according to the reaction SO3 − + H3 O + ↔ SO3 H + H2 O, which was found to be an essential part of the hydronium diffusion mechanism. This suggests there are optimal hydration conditions that allow the sulfonate end groups to take an active part in the hydronium diffusion mechanism, resulting in high hydronium conductivity. We expect that the results of this study could help guide synthesis and experimental characterization used to design new PEM materials with high hydronium conductivity.